Desain Magic Box dalam Meningkatkan Pemahaman Kegiatan Ekonomi pada Peserta Didik - Moh Sutomo; Siti Harirotun Nisa; Maghfirotul Firmaning Lestari (IAIN Madura, 2025)
This study aims to develop an effective Magic Box learning media to improve students' motivation and understanding of Natural Science and Social Studies (IPAS) in elementary schools. The purpose of this study is to develop an effective Magic Box learning media and measure its feasibility and effectiveness in improving students' motivation and understanding of IPAS. This study uses a Research and Development (R&D) approach with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. Information sources in this study were obtained through qualitative and quantitative data, with data collection instruments in the form of observations, questionnaires, documentation, and tests (pre-test and post-test). The data analysis technique used is qualitative and quantitative analysis. The results of the study show that the Magic Box learning media has high feasibility and effectiveness in improving students' motivation and understanding of IPAS. This media can also increase students' curiosity and encourage students to take an active role in the learning process. The use of Magic Box media can become an effective and enjoyable alternative learning media.